FY2018-FY2020 Medium-Term Budget. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2017)
The Fund has been operating under a flat real resource envelope for the past six years. With continued efforts to maximize the use of available resources, spending in FY 17 is projected to reach 99 percent of the net administrative budget, and a low vacancy rate has helped stabilize overtime at 11 percent. Internal savings and reallocations have allowed the Fund to dedicate more resources to country work, including capacity development, without requiring an increase in the approved budget-apart from USD 6 million provided in FY 17 to cover rising security costs. An unchanged real net administrative budget in FY 18, despite deeper Fund engagement in a number of areas, as well as increased costs for corporate modernization. Accordingly, the budget proposal incorporates significant savings from reallocations and efficiency gains to fund new demands, as well as a further increase in the upfront allocation of carry-forward funds by about USD 10 million. The broad themes of the proposal are: (i) more intensive country work with a shift from surveillance to programs, but net savings in field offices; (ii) significant policy and analytical work on the financial sector and the role of the Fund (global safety net, facilities, and quotas), albeit less than in FY 17, with more work on structural issues and new challenges; (iii) funding for transforming IT and HR services, offset by central savings; and (iv) enhanced risk mitigation and knowledge management (KM), with the establishment of a KM unit to support cross-country analysis and knowledge transfer. At this stage, a flat resource envelope is assumed also for the medium term, contingent on continued reprioritization and a broadly unchanged global economic environment. Upward pressure on resources will arise from growing capacity development activities and certain revenue losses. Savings are expected from the TransformIT initiative and internal efficiency gains. But for the budget to remain flat, the Fund will need to continuously reprioritize and adjust its activities to make room for new demands. Even then, a more challenging global environment, with a further ramping up of Fund lending, or significant demands for deeper engagement in other areas, would put significant strains on resources over the medium term. The proposed capital budget envelope for FY 18-20 remains broadly unchanged from current levels. Some frontloading, however, is planned for the first two years, due to the cyclical nature of these investments and to accommodate strategic IT projects.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet